Regional and temporal variability of sinking organic matter in the subtropical northeast Atlantic Ocean: A biomarker diagnosis - Alonso-González, Iván J.; Arístegui, J.; Lee, Cindy; Calafat, Antoni (Biogeosciences, 2011)
Sinking particles through the pelagic ocean have\nbeen traditionally considered the most important vehicle by\nwhich the biological pump sequesters carbon in the ocean\ninterior. Nevertheless, regional scale variability in particle\nflux is a major outstanding issue in oceanography. Here, we\nhave studied the regional and temporal variability of total\nparticulate organic matter fluxes, as well as chloropigment\nand total hydrolyzed amino acid (THAA) compositions and\nfluxes in the Canary Current region, between 20?30_\nN, during\ntwo contrasting periods: August 2006, characterized by\nwarm and stratified waters, but also intense winds which enhanced\neddy development south of the Canary Islands, and\nFebruary 2007, characterized by colder waters, less stratification\nand higher productivity. We found that the eddyfield\ngenerated south of the Canary Islands enhanced by >2\ntimes particulate organic carbon (POC) export with respect to\nstations (FF; far-field) outside the eddy-field influence. We\nalso observed flux increases of one order of magnitude in\nchloropigment and 2 times in THAA in the eddy-field relative\nto FF stations. Principal Components Analysis (PCA)\nwas performed to assess changes in particulate organic matter\ncomposition between stations. At eddy-field stations,\nhigher chlorophyll enrichment reflected ?fresher? material,\nwhile at FF stations a higher proportion of pheophytin indicated\ngreater degradation due to microbes and microzooplankton.\nPCA also suggests that phytoplankton community\nstructure, particularly the dominance of diatoms versus\ncarbonate-rich plankton, is the major factor influencing the\nPOC export within the eddy field. In February, POC export\nPOC export within the eddy field. In February, POC export \nfluxes were the highest ever reported for this area, reaching\nvalues of _15 mmolCm?2 d?1 at 200m depth. Compositional\nchanges in pigments and THAA indicate that the\nsource of sinking particles varies zonally and meridionally\nand suggest that sinking particles were more degraded at\nnear-coastal stations relative to open ocean stations.